2015
DOI: 10.1109/jbhi.2015.2432454
|View full text |Cite
|
Sign up to set email alerts
|

Posture and Activity Recognition and Energy Expenditure Estimation in a Wearable Platform

Abstract: The use of wearable sensors coupled with the processing power of mobile phones may be an attractive way to provide real-time feedback about physical activity and energy expenditure (EE). Here we describe the use of a shoe-based wearable sensor system (SmartShoe) with a mobile phone for real-time recognition of various postures/physical activities and the resulting EE. To deal with processing power and memory limitations of the phone, we compare use of Support Vector Machines (SVM), Multinomial Logistic Discrim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 27 publications
1
49
0
Order By: Relevance
“…Kwapisz et al (108) found similar result (91.7%) with a smartphone in detecting six activities of daily life. Several studies reported great accuracy in estimating AEE compared with IC (RMSE = 0.69–1.25 METs and MSE = 0.25 METs) and a lower error as compared to another method (MSE = 2.05 METs for the Actiheart) (109111). Inertial sensors consisting of a three dimensions accelerometer and gyroscope and a magnetometer can be used to identify the type of activity performed like previous accelerometers (112).…”
Section: Assessment Of Energy Expenditure In Subjects With Dmmentioning
confidence: 99%
“…Kwapisz et al (108) found similar result (91.7%) with a smartphone in detecting six activities of daily life. Several studies reported great accuracy in estimating AEE compared with IC (RMSE = 0.69–1.25 METs and MSE = 0.25 METs) and a lower error as compared to another method (MSE = 2.05 METs for the Actiheart) (109111). Inertial sensors consisting of a three dimensions accelerometer and gyroscope and a magnetometer can be used to identify the type of activity performed like previous accelerometers (112).…”
Section: Assessment Of Energy Expenditure In Subjects With Dmmentioning
confidence: 99%
“…Figure 3a shows a picture of SmartStep insole [80] and the associated Android application for daily activity monitoring. PC post processing for activity classification using neural network [81], decision trees [74], and support vector machines (SVM) [81] PC post processing for activity classification utilizing multinomial logistic discrimination (MLD) [80] PC post processing for activity classification using decision trees [78] and linear discriminant analysis [78] Four different decision trees to classify activity from four sets of sensors (left shoe, right shoe, accelerometer, and gyroscope. Majority voting to decide the activity [79] Activities [55,82] and healthy subjects [73,81] Initial validation study on five healthy subjects [80] Validated on five healthy subjects and one subject with amputee NA Accuracy~99% 96% 98.4%~99%…”
Section: Posture and Activity Recognition And Energy Expenditure Estmentioning
confidence: 99%
“…In terms of data processing, as reported in [81], support vector machines (SVM), being computationally expensive, are not suitable for implementing in portable electronic devices, such as smartphones, for real-time activity classification purposes. The study in [81] also reports that activity prediction models based on multinomial logistic discrimination (MLD) is computationally less expensive in terms of required memory space and execution time, and performs equally well in terms of accuracy, as compared to SVM.…”
Section: Posture and Activity Recognition And Energy Expenditure Estmentioning
confidence: 99%
See 2 more Smart Citations